Effect of confining pressure on hysteretic soil-water characteristic curves of sandy soils - Peter, Sarah (Nanyang Technological University, 2021)
The Soil-Water Characteristic Curve (SWCC) depicts the relationship between water content and soil suction. Using the Tempe cell and volumetric pressure plate extractor, the drying and wetting SWCC for sands with different grain size distributions were determined, respectively, under zero confining pressure. The flexible wall apparatus was used to obtain the drying and wetting SWCC of the soils under a net confining pressure of 10 kPa. Experimental results were curve-fitted using Fredlund and Xing (1994) equation. From the results, a number of observations were made. Sands with lower D10 values had higher air-entry values. Fredlund and Xing (1994) SWCC equation parameter a increases with air-entry values. The relationship between Fredlund and Xing (1994) SWCC equation parameters m and n were found to have a similar relationship as Chin et al. (2010). Under confining pressure, the sands had a slightly higher air-entry value, while the initial water content was reduced. The drying SWCCs at 0 kPa and 10 kPa confining pressures merged into a single curve, at suctions greater than 2 kPa. A similar trend was observed for the wetting SWCCs.